Impact of Mean Annual Temperature on Nutrient Availability in a Tropical Montane Wet Forest - Litton, Creighton M.; Giardina, Christian P.; Freeman, Kristen R.; Selmants, Paul C.; Sparks, Jed P. (Frontiers in Plant Science, 2020)
Despite growing understanding of how rising temperatures affect carbon cycling, the impact of long-term and whole forest warming on the suite of essential and potentially limiting nutrients remains understudied, particularly for elements other than N and P. Whole ecosystem warming experiments are limited, environmental gradients are often confounded by variation in factors other than temperature, and few studies have been conducted in the tropics. We examined litterfall, live foliar nutrient content, foliar nutrient resorption efficiency (NRE), nutrient return, and foliar nutrient use efficiency (NUE) of total litterfall and live foliage of two dominant trees to test hypotheses about how increasing mean annual temperature (MAT) impacts the availability and ecological stoichiometry of C, N, P, K, Ca, Mg, Mn, Fe, Zn, and Cu in tropical montane wet forests located along a 5.2°C gradient in Hawaii. Live foliage responded to increasing MAT with increased N and K concentrations, decreased C and Mn concentrations, and no detectable change in P concentration or in foliar NRE. Increases in MAT increased nutrient return via litterfall for N, K, Mg, and Zn and foliar NUE for Mn and Cu, while decreasing nutrient return for Cu and foliar NUE for K. The N:P of litterfall and live foliage increased with MAT, while there was no detectable effect of MAT on C:P. The ratio of live foliar N or P to base cations and micronutrients was variable across elements and species. Increased MAT resulted in declining N:K and P:K for one species, while only P:K declined for the other. N:Ca and N:Mn increased with MAT for both species, while N:Mg increased for one and P:Mn increased for the other species. Overall, results from this study suggest that rising MAT in tropical montane wet forest: (i) increases plant productivity and the cycling and availability of N, K, Mg, and Zn; (ii) decreases the cycling and availability of Mn and Cu; (iii) has little direct effect on P, Ca or Fe; and (iv) affects ecological stoichiometry in ways that may exacerbate P–as well as other base cation and micronutrient – limitations to tropical montane forest productivity.